Investigation of PV Connected Multilevel Cascaded H-Bridge Inverter Using Disposition Techniques - Khan Patan, Muzeeb; Udaya Bhanu, P; D. Azahar Ahmed, M (International Journal of Engineering and Technology, 2018)
Inverters have many Technological improvements in their maximum power handling capabilities by using renewable energy sources. Multilevel inverters give effective and efficient interface for renewable energy sources and perform Transformer-less operation and increase the power quantity and quality of voltage of the PV system. In this paper, the benefits of H-bridge inverters including the total harmonic distortions are discussed. This paper has primarily focused on Sinusoidal PWM and worked on the carrier based phase disposition techniques. The performances of modulation schemes are compared. Simulations were done using MATLAB Simulink for the given PWM techniques.Â Â